Multi-physics investigation of a GaAs solar cell based PV-TE hybrid system with a nanostructured front surface. (August 2021) - Hu, Yi-Huang; Li, Ming-Jia; Zhou, Yi-Peng; Xi, Huan; Hung, Tzu-Chen
Highlights: A numerical model of GaAs-TE system with a nanostructured front surface. Multi-physics coupling effects of nanostructure on GaAs-TE system performance. The reflectance reduction in 0.28 ~ 0.875 μm improves system power by 374.3 W·m −2 . The reflectance reduction in 0.875 ~ 2.5 μm improves system power by 79.1 W·m −2 . Nanostructure with low reflectance in full spectrum is advised for system. Abstract: Tandem PV-TE hybrid system is an effective full solar-spectrum utilization method. Nanostructured front surface can make the system absorb more solar light, thereby generating more carriers and more heat. The heat will decrease photovoltaic efficiency but increase thermoelectric efficiency. Therefore, it's necessary to clarify the combined effect of nanostructure's full-spectrum characteristics on PV-TE hybrid system. In this study, a multi-physics coupling model of a GaAs solar cell based PV-TE hybrid system with a nanostructured front surface was built and validated. The numerical results show that the system output power of nanostructure with a 1.8% average reflectance in 0.28 ~ 0.875 μm is 374.3 W·m −2 greater than that with a 8.7% average reflectance and the system output power of nanostructure with a 2.6% average reflectance in 0.875 ~ 2.5 μm is 79.1 W·m −2 greater than that with a 8.1% average reflectance under 100 concentration ratio. It means that both the reductions of reflectance in 0.28 ~ 0.875 μm and in 0.875 ~ 2.5 μm can effectively improve the system output power. Therefore, nanostructure with low reflectance in full spectrum (not only in short wavelengths) is advised for a GaAs solar cell based PV-TE hybrid system.